2015
DOI: 10.4238/2015.june.11.8
|View full text |Cite
|
Sign up to set email alerts
|

Association of MDR1 C3435T and C1236T single nucleotide polymorphisms with male factor infertility

Abstract: ABSTRACT. Infertility affects 1 in 6 couples and approximately 1 in 25 men. Male factor infertility is a major cause of spermatogenic anomalies, the causes of which are largely unknown. Impaired reproductive functions in men might result from physiological, genetic, and/or environmental factors such as xenobiotics. The multi-drug resistance1 (MDR1) gene encodes a P-glycoprotein which has a role in the active transport of various substrates providing protection of somatic cells from potentially toxic substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Infertility is undoubtedly a complicated pathological condition affecting 4% to 7% of the male population across the globe and is demonstrated as a broad range of heterogeneous phenotypes, from congenital or acquired urogenital abnormalities, endocrine disturbances, and immunological factors to spermatogenic quantitative and qualitative defects. It has been observed that 15% of infertile males have a genetic defect ( Aydos et al, 2015 ; Xavier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infertility is undoubtedly a complicated pathological condition affecting 4% to 7% of the male population across the globe and is demonstrated as a broad range of heterogeneous phenotypes, from congenital or acquired urogenital abnormalities, endocrine disturbances, and immunological factors to spermatogenic quantitative and qualitative defects. It has been observed that 15% of infertile males have a genetic defect ( Aydos et al, 2015 ; Xavier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The product of the MDR1 gene is P-glycoprotein, which is a probable link between the environmental and genetic factors that lead to the development of male infertility ( Droździk al., 2009 ). It has a shielding role and removes toxic substances such as xenobiotics from cells and prevents their buildup within cells, which serves as a protective measure for the organism ( Aydos et al, 2015 ). Xenobiotics, including pesticides, act as a substrate for P-glycoprotein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C1236T is a synonymous mutation that does not cause amino acid change (Kozhakhmetov et al 2013). While, C3435T is the only silent polymorphism currently identified, which may affect the expression of Pgp in different organs/tissues and even in different races (Aydos et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…but frequent polymorphisms (SNPs) that affect oxidative stress (GSTT1, GSTM1, SOD 2), and the detoxifying capacity (CYP2D6, CYP2C9, CYP2C19, NAT 2). [28,29] Clinically, this syndrome multifactorial and multisystemic, appears with a slowing of cognitive behavioral development (isolation, indifference, loss of contact with peers and family members) regression of the word, self behaviors and hetero aggressive and a long line of organic disorders, affecting intestinal function, immune and energy metabolism. [30] Since 1995 it is stated in the international arena the multidisciplinary approach for the prevention and treatment of developmental disorders (Defeat Autism Now, DAN!…”
mentioning
confidence: 99%